Notes on How to Consider The Relationship Between Medicine and Public Authorites - González Quirós, José Luis (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
In order to examine relations between political authorities and the health system we need a historical view that allows us to understand the drift of the ever expanding health system under liberal systems and the introduction of new concepts such as the right to health under so-called Welfare States. State appropriation of citizens’ health, through health systems, changes the paradigm of the doctor-patient relationship as understood traditionally and historically, and makes us cautious about what may be a threat to our individual liberties, with a disproportionate health service and states that intervene directly in the lives of their citizens not only as regards the law but also their health and bodies. This all needs to be analyzed unreservedly and we must be careful that the right to health does not become an instrument of power and control by states over citizens, thus diminishing our liberties.